The Lightning Conductor Discovers America - Williamson, C. N. (Charles Norris), 1859-1920; Williamson, A. M. (Alice Muriel), 1869-1933 (Salt Lake City, UT : Project Gutenberg, 2009)
"The Lightning Conductor Discovers America" by C. N. Williamson and A. M. Williamson is a novel written in the early 20th century. The story revolves around the adventures of the Hon. Mrs. Winston and her husband, who journey to America and encounter various characters, including a mysterious young man named Peter Storm. The narrative explores themes of identity, social class, and romance against a vibrant backdrop of transatlantic travel. The beginning of the novel introduces Mrs. Winston aboard the SS. Evangeline, as she writes a letter to her friend detailing their voyage and her excitement about visiting America. She reflects on her husband Jack's recent recovery from war injuries and their plans to visit her inherited property on Long Island. Among the characters introduced is the enchanting Miss Patricia Moore, a young woman returning to America after being raised in a convent school in France, and the enigmatic Peter Storm, whose past experiences and true identity pique the curiosity of the other passengers. The opening sets up a compelling mix of social intrigue, personal challenges, and unexpected connections that promise an engaging exploration of life in America during this time. (This is an automatically generated summary.)
Release date is 2009-06-09
E-text prepared by Woodie4, Suzanne Shell, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Automobiles -- Fiction